EFFECT OF AUDITOR’S INDEPENDENCE ON AUDIT QUALITY: EVIDENCE FROM DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2023)
The study determined the effect of auditor’s independence on audit quality of deposit money banks in Nigeria. Specifically, the study sought to ascertain the effect of audit committee independence, audit fees and audit tenure on audit quality of deposit money banks in Nigeria. The study adopted Ex-Post Facto research design. All the quoted deposit money banks were used as sample for the study. Data were extracted from annual reports and accounts of the sampled banks. Simple regression analysis was used to test the formulated hypotheses with aid of E-view version 9.0. Based on analysis, the study found that audit committee independence has a positive insignificant effect on audit quality of quoted Nigerian deposit money banks.  Also that audit fees have a positive effect on audit quality of quoted Nigerian deposit money banks, but not statistically significant. The researcher therefore recommended among others that the auditor should be remunerated on the basis of work experience, qualification, duration of the audit assignment, and background profile.
Keywords: Auditor’s independence; Audit quality; Deposit money banks